Developable mechanisms on regular cylindrical surfaces. (December 2019) - Greenwood, Jacob R.; Magleby, Spencer P.; Howell, Larry L.
Highlights: Developable mechanisms can achieve high functionality and compact storage. Cylindrical developable mechanisms align links with a cylindrical surface. Equations aid in the kinematic analysis of cylindrical developable mechanisms. Intramobile, Extramobile, and Transmobile mechanisms categorize unique behavior. Guidelines for designing four-bar cylindrical developable mechanisms are presented. Abstract: Developable mechanisms can provide high functionality and compact stowability. This paper presents engineering models to aid in the design of cylindrical developable mechanisms. These models take into account the added spatial restrictions imposed by the developable surface. Equations are provided for the kinematic analysis of cylindrical developable mechanisms. A new classification for developable mechanisms is also presented (intramobile, extramobile, and transmobile) and two graphical methods are provided for determining this classification for single-DOF planar cylindrical developable mechanisms. Characteristics specific to four-bar cylindrical developable mechanisms are also discussed.